Orally active prostacyclin analogue beraprost sodium in patients with chronic kidney disease: a randomized, double-blind, placebo-controlled, phase II dose finding trial. Issue 1 (December 2015) - Koyama, Akio; Fujita, Toshiro; Gejyo, Fumitake; Origasa, Hideki; Isono, Masanao; Kurumatani, Hajimu; Okada, Kiyonobu; Kanoh, Hiroyuki; Kiriyama, Takashi; Yamada, Shunsuke
Abstract Background Evidence increasingly points to the importance of chronic hypoxia in the tubulointerstitium as a final common pathway to end-stage renal disease (ESRD). Beraprost sodium (BPS) is an orally active prostacyclin (PGI2 ) analogue demonstrating prevention of the progression of chronic kidney disease (CKD) in various animal models by maintaining renal blood flow and attenuating renal ischemic condition. Methods This multicenter, randomized, double-blind, placebo-controlled, phase II trial was designed to determine the recommended dose of the sustained-release form of BPS (TRK-100STP 120 μg/day or 240 μg/day) in Japanese patients with CKD. TRK-100STP was administered to a total of 112 patients. The primary efficacy endpoint was the difference in the slope of the regression line of reciprocal of serum creatinine (1/SCr) over time, obtained by the least-squares method. Results Regarding the primary endpoint, statistical superiority of TRK-100STP 240 μg over placebo was not confirmed and so a recommended dose was not determined. Compared to placebo, however, the slope of regression line of 1/SCr, elevation of SCr and serum cystatin C during the treatment period revealed greater improvement at 120 μg, at both doses, and at 240 μg, respectively. In terms of safety, both TRK-100STP treatment groups were well tolerated. Conclusions Although the study failed to meet the primary endpoint, results indicate that TRK-100STP may potentially prevent the decline in renal function of CKD patients independent of blood pressure or urinary protein levels. Trial registration NCT02480751 . June 21, 2015.